Extreme25 Expedition Report - Panieri, Giuliana; Argentino, Claudio; Amaglio, Giulia; Bagøien, Gry; Barrenechea Angeles, Ines; Basili, Marco; Burkitt-Gray, Mary; Cicerôn Lukas Pérez, Bjørn; Cuffaro, Marco; Dögg Jonsdottir, Hekla; Eilertsen, Mari Heggernes; Faizeva, Kamila; et al. (Septentrio Reports, 2026)
The Extreme25 expedition is conducted as a continuation of Extreme24 and within the umbrella of EXTREMES UArctic project (UA 06/2024), a collaboration between UiT-The Arctic University of Norway (Department of Geosciences), the University of Copenhagen (Department of Arts and Cultural Studies), and the University of Iceland Research Centre in Þingeyjarsveit. The Extreme25 expedition brought together scientists, students, media experts, and artists from around the world to explore extreme environments. The international team included geologists, geophysicists, geochemists, methane specialists, and marine ecologists, and for the first time, the EXTREME expedition also hosted an active delegation from the National Research Council of Italy (CNR), representing multiple institutes and disciplines. The various groups included a team of chemists and engineers from Woods Hole Oceanographic Institution; researchers from EXTREMES, scientists from the University of Bergen contributing expertise in deep-sea chemosynthesis-based ecosystems; scientists from University Milano Bicocca supporting the high-resolution mapping effort; microbiologists from University of Naples Federico II; micropalaeontologists from University of Vienna; anthropologists and artists studying human–polar interactions and new modes of science communication. The overarching goal of the expedition was to explore deep-sea habitats of cold seeps and hydrothermal vents within Norwegian waters, from the Fram Strait to the Barents Sea, and collect samples that can tell us about the geodynamics and biology of these extreme environments. The expedition has been developed by leveraging the extensive knowledge gained from two significant projects funded by the Norwegian Research Council: CAGE (Centre for Arctic Gas Hydrate, Environment and Climate) and AKMA (Advancing Knowledge of Methane in the Arctic), hosted at the Department of Geosciences at UiT.